Managing Islamic Endowments (Waqf): Legal Challenges and Strategic Approaches for Sustainable Development - Fauzan Ulwan Fadhlurrahman; Muhammad Diaz Wahyu Darmansyah; Yogi Permana Adi Citra (Journal of Islamic Law and Legal Studies, 2025)
This research explores the significance of waqf (Islamic endowment) management in achieving sustainable development, emphasizing the legal and managerial obstacles that impede its optimal performance. Although waqf has historically played a vital role in areas such as education, healthcare, and poverty reduction, modern administration is challenged by disjointed legal systems, outdated policies, and inadequate governance structures. These issues contribute to inefficiency, a lack of transparency, and declining confidence among donors. Applying a qualitative library research method, the study systematically examines scholarly sources, legal texts, and institutional records to assess how legal reform and strategic governance can enhance waqf operations. The analysis highlights the importance of aligning Islamic legal principles with contemporary management approaches—such as performance planning, financial innovation, and clear accountability measures—to improve both impact and efficiency. Moreover, the study stresses the urgent need for legal restructuring and human capital development within waqf institutions to ensure long-term viability and professionalism. By overcoming legal and organizational shortcomings, waqf can be transformed into a dynamic and sustainable financial instrument that supports the Sustainable Development Goals (SDGs). This research offers valuable academic and policy insights into creating effective, transparent, and Shariah-compliant waqf frameworks suited to modern socio-economic challenges.